2019
DOI: 10.3390/ijerph16224500
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Forestry Workers in Guadalajara Province (Spain) for Antibodies to Lymphocytic Choriomeningitis Virus, Hantavirus, Rickettsia spp. and Borrelia burgdorferi

Abstract: Exposure to Lymphocytic choriomeningitis virus (LCMV), hantaviruses, Rickettsia spp. and Borrelia burgdorferi among forestry workers from a province in central Spain (Guadalajara) was examined by serological screening. This is the first such study in this rural area, where people often live and work in proximity to domestic and wild animals. Immunofluorescent analyses of the serum of 100 forestry workers detected IgG antibodies to LCMV in 2% (CL 95% 0.55%–7.0%) of this population, to hantaviruses in 4% (CL 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…After applying the inclusion and exclusion criteria (Figure 1), a total of 42 articles were included in the analyses and summarized, with a total of 28 estimates on agricultural workers and 22 on forestry workers, from 20 studies reporting on agricultural workers , 14 on forestry workers [39][40][41][42][43][44][45][46][47][48], and eight further studies reporting on both occupational groups [15,18,[21][22][23]49]. In one of the earlier studies, authors reported agricultural and forestry workers as a single exposure group, and the estimates were therefore included in both sub-analyses [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After applying the inclusion and exclusion criteria (Figure 1), a total of 42 articles were included in the analyses and summarized, with a total of 28 estimates on agricultural workers and 22 on forestry workers, from 20 studies reporting on agricultural workers , 14 on forestry workers [39][40][41][42][43][44][45][46][47][48], and eight further studies reporting on both occupational groups [15,18,[21][22][23]49]. In one of the earlier studies, authors reported agricultural and forestry workers as a single exposure group, and the estimates were therefore included in both sub-analyses [30].…”
Section: Resultsmentioning
confidence: 99%
“…Estimates on forestry workers were available only from European [15,[21][22][23]30,[40][41][42][43][44][45][46][47]49,55,[57][58][59][60] and American regions [18,48]. Two of the European reports [45,59] seemly reported on the same occupational groups (i.e., forestry workers from Poland), focusing either on PUUV [45] or DOBV [59] but no specific disclosure was provided by study authors.…”
Section: Studies On Forestry Workersmentioning
confidence: 99%
“…Even though there is substantial evidence that certain occupational groups (e.g., farmers, forestry workers, etc.) are at greater risk of infection and, also, exhibit higher antibody prevalence than control groups [ 1 , 5 , 9 , 38 , 39 ], only 64.1% and 65.5% of participants acknowledged a higher risk for hantavirus infections among agricultural and forestry workers, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Second, while we specifically assessed the KAP of medical professionals, the available reports previously focused on residential and occupational groups, of variable health literacy. Eventually, it should be stressed that we specifically stressed the KAP of OP, whose potential importance in the management of hantavirus infections has been recently and strongly addressed [ 9 , 47 , 48 ], even though their actual understanding of these pathogens and related clinical syndromes largely remains undefined in both high- and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation